If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -16 = -2z Combine like terms: 6 + -16 = -10 -10 = -2z Solving -10 = -2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '2z' to each side of the equation. -10 + 2z = -2z + 2z Combine like terms: -2z + 2z = 0 -10 + 2z = 0 Add '10' to each side of the equation. -10 + 10 + 2z = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 2z = 0 + 10 2z = 0 + 10 Combine like terms: 0 + 10 = 10 2z = 10 Divide each side by '2'. z = 5 Simplifying z = 5
| 60x=210 | | Y^2-15=3y+25 | | 4x+5y=841 | | -5x+-15x=-30 | | 4(t+8)-35= | | -3(f-4)=36 | | 47-(7)2= | | 7w-9x=2w+3x | | (5x-10)+(x+1)=180 | | 4(6y+3)-16y=52 | | X(.10)=1375 | | -3x+8y=-38 | | 12*x-(2*x+18)=2(5*x-9) | | 8+2n= | | 8(f-2)+4-2f=3f+36 | | 5y-4+y=59+2y-5y | | 7hn=5 | | 7(m-6)=4 | | -2y+4y=10 | | 15c^2+14c+3=0 | | whatdoesy= | | 6(3x-4)+54=3(x+11) | | 1.2x+7=13+x | | 14v=0 | | 5(x-2)-3*x=2(x-6) | | 81x^2+10=110 | | r+2.82=6.82 | | 9n=h | | 14+23=35+16 | | 5y+3x=349 | | f+2=20 | | 9(x+3)=4*x-3 |